EP.TU.785Quality Improvement Project: Improving Oxygen therapy prescription in surgical inpatients. (28th October 2021) - Hamid, Mohammed; Al-Saket, Laith; Rawashdeh, Arab; Sudarsanam, Raman
Abstract: Aims: The 2015, British Thoracic Society (BTS) Oxygen audit demonstrated that 42% of hospital inpatients were using Oxygen without a prescription. National and local standards state that Oxygen, as a drug, should be routinely prescribed and checked along with regular medications and VTE risk assessment. Our baseline audit conducted over a two month period on the surgical wards of a large city hospital revealed that 78% of patients were not being prescribed oxygen. We set a SMART aim to increase the percentage of surgical inpatients being prescribed oxygen by 20% each month. Methods: We used the trust e-prescription software to record our data, with three-stage verification and subsequent senior analysis of data. The three primary drivers identified were factors intrinsic to the department: lack of standard awareness, education and safety-net to ensure sustainability. To tackle these in-turns, we designed three PDSA cycles: Departmental poster, seminar with induction material, and system checklist notification. Results: Following our first PDSA cycle, the mean percentage increased from 22% to 60%. Using projection analysis, we anticipate this to increase to > 75% after the second PDSA cycle, and >95% after PDSA3, with 100% sustainability one year later. Conclusion: Our results to-date show that practice standards have improved following our first PDSA cycle, indicating that awareness played an important role. We predict that education will play an equal role; and given the research supporting the implications of checklists, we forecast that this later element will be the ultimatum leading to 100% sustainability of patients receiving oxygen prescription.